A Mild Method for the Replacement of a Hydroxyl Group by Halogen: 4. Practical Synthesis of Cyclic β-Halovinylketones under Neutral Conditions - Munyemana, François; Ghosez, Léon (Synthesis, 2023)
The replacement of a hydroxyl group by a halogen is a pivotal organic functional group transformation. Existing procedures often require acidic conditions or lack sustainability and atom economy. We have previously shown that tetramethyl-α-haloenamines (TMXE) or 2,2-dimethyl-1-halo-1-diisopropylamines (DIXE) react with a wide variety of hydroxyl-containing molecules to yield the corresponding halides under very mild conditions and with high atom economy. We now show that the deoxyhalogenation reactions of the enol tautomers of cyclic1,3-diketones and of 2-hydroxymethylene cycloketones can also be performed with TMCE or DIXE to yield β-halo-α,β-unsaturated ketones in excellent yields. The reactions are regioselective and in some cases stereoselective. The reaction is also successful with acetylacetone but the yield is only moderate. β-Ketoesters are not reactive. The method favorably compares to the best existing methods: It is more general, occurs under very mild conditions, which should allow acid-sensitive functional groups such as ketals, esters, ethers, etc., to be tolerated, and, above all, is quite sustainable (no toxic reagents or products).
Keywords: deoxyhalogenation; α-chloroenamines; α-bromoenamines; α-iodoenamines; cyclohexane-1,3-diones; cyclopentane-1,3-diones; β-halovinyl ketones